ELSA – A Method for Medical Knowledge Acquisition and Processing to Aid Medical Reasoning - Ruszkowski, J. (Methods of Information in Medicine, 1986)
Experts’ Lattice-Structured Acquirements (ELSA) is a method of medical experts’ knowledge management which aims at aiding clinical problem solving by various ways and forms, from simple procedures of clinical data evaluation to computer-aided consultation and teaching systems in all fields of medicine. The concept of the ELSA method is based upon the assumption of the relational nature of medical reasoning and clinical decision making in man. Furthermore, there are some reasons to judge that physicians rather use qualitative clinical data or quantitative ones converted into qualitative ones in their clinical thinking. Two stages of method performance have been described: First, the data acquisition concerned with total decomposition of a medical problem to as simple as possible questions to the experts and, second, the composition procedure to be applied to the knowledge structures obtained as experts’ answers. The paper deals with algorithms of how to record and check experts’ knowledge data obtained according to ELSA rules and how to use them for setting up an order relation in diagnostic hypotheses set according to the syndrome of symptoms and signs considered. Some practical applications and evaluations of the method are mentioned.
Keywords: Medical Knowledge; Decision Making; Computer-aided Diagnosis; Gynecology; Differential Diagnosis